Infection caused by Klebsiella pneumoniae ST11 in a patient after craniectomy - Ojdana, Dominika; Kochanowicz, Jan; Sacha, Paweł; Sieńko, Anna; Wieczorek, Piotr; Majewski, Piotr; Hauschild, Tomasz; Mariak, Zenon; Tryniszewska, Elżbieta (Folia microbiologica, 2020)
Klebsiella pneumoniae infections have always been an important problem in public health, but today, the increasing resistance of these bacteria to antibiotics due to β-lactamases production has renewed interest in K. pneumoniae infections. The aim of the study was to present a case of a neurosurgical patient with multidrug-resistant K. pneumoniae ST11 infection after craniectomy. Four K. pneumoniae isolates from various clinical materials of the patient undergone identification and susceptibility testing with the Vitek2 system. Tests for β-lactamases production were performed according to EUCAST guidelines. Strains were analyzed for bla genes responsible for β-lactamase production (blaTEM, blaSHV, blaCTX-M, blaVIM, blaIMP, blaNDM, blaKPC, blaOXA-48) using PCR. Moreover, the genetic relatedness of these isolates was determined by pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). All tested strain presented multidrug resistance. The highest susceptibility was observed for imipenem, meropenem, and ertapenem. The strain isolated from the nervous system was ESBL-positive with blaSHV-11, blaTEM-1, and blaCTX-M-15 genes. Additionally, the strain from urine was blaKPC-3-positive. Molecular typing revealed that all strains belonged to the same clone and identified two PFGE profiles. The analysis of MLST allelic profile showed that tested K. pneumoniae strains belonged to ST11. Identification of ST11 K. pneumoniae as etiological factor of infection unfavorably impacts on prognosis among neurosurgical patient after craniectomy.
Keywords: pulzní gelová elektroforéza; mikrobiální testy citlivosti; beta-laktamasy; mladý dospělý; Tomography, X-Ray Computed; Klebsiella Infections; lidé; Anti-Bacterial Agents; multilokusová sekvenční typizace; Electrophoresis, Gel, Pulsed-Field; beta-Lactamases; infekce bakteriemi rodu Klebsiella; Humans; Microbial Sensitivity Tests; Male; fatální výsledek; Fatal Outcome; Young Adult; mnohočetná bakteriální léková rezistence; Bacterial Typing Techniques; techniky typizace bakterií; Drug Resistance, Multiple, Bacterial; Multilocus Sequence Typing; Craniotomy; mužské pohlaví; antibakteriální látky; Klebsiella pneumoniae; kraniotomie; počítačová rentgenová tomografie